2016
DOI: 10.3390/molecules21050656
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Activity of Alkyl Nitroderivatives of Hydroxytyrosol

Abstract: A series of alkyl nitrohydroxytyrosyl ether derivatives has been synthesized from free hydroxytyrosol (HT), the natural olive oil phenol, in order to increase the assortment of compounds with potential neuroprotective activity in Parkinson's disease. In this work, the antioxidant activity of these novel compounds has been evaluated using Ferric Reducing Antioxidant Power (FRAP), 2,2 1 -azinobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), and Oxygen Radical Scavenging Capacity (ORAC) assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Based on these grounds, diverse HT derivatives have been synthesized. [18][19][20][21][22] The bioactivities of these HT derivatives have been studied, including their antiplatelet aggregation capacity, 4,42,43 neuroprotective activity, 44 DNA oxidative damage protection, 30 cytoprotection, 45 antiinflammatory effects, 38,46 and anticancer activity. 12,47 Most of these derivatives have shown to maintain or even improve the diverse activities of free HT, mainly due to the better lipophilic/hydrophilic balance exhibited by these derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these grounds, diverse HT derivatives have been synthesized. [18][19][20][21][22] The bioactivities of these HT derivatives have been studied, including their antiplatelet aggregation capacity, 4,42,43 neuroprotective activity, 44 DNA oxidative damage protection, 30 cytoprotection, 45 antiinflammatory effects, 38,46 and anticancer activity. 12,47 Most of these derivatives have shown to maintain or even improve the diverse activities of free HT, mainly due to the better lipophilic/hydrophilic balance exhibited by these derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, introduction of a nitro group (NO 2 ) in the cathecolic ring of HT induces a significant increase in their antioxidant activities, 20,21 maintaining a high in vitro bioavailability and hepatic metabolism. 39 Finally, a recent study has shown that some nitroderivatives associated with the Mediterranean diet have an important cardioprotective effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In addition, olive oil contains saturated fatty acids (~14%), polyunsaturated fatty acids (~9%), alpha-tocopherol, and vegetable mucilage. [5,6] Moreover, olive oil contains several potent bioactive compounds such as antioxidant polyphenols (oleuropein [8,9] , hydroxytyrosol [10,11] , and tyrosol [12,13] ), antioxidant flavonoids (luteolin [14,15] and apigenin [16,17] ), and other bioactive organic molecules, including squalene. [18,19] These compounds have been directly and indirectly linked to various health problems such as cancer [2,20] , coronary heart disease [21,22] , and reproductive capability.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally similar compounds, differentiating only by an atom or position in the molecule, may present differences related to their physicochemical properties and therefore result in distinct biological activities (Tavares, 2004). Although the length of the groups may influence the potency of the compound, for example, shorter chains resulting in more active compounds than longer chains (Gallardo et al, 2016;Nguyen et al, 2015), this pattern was not observed for indole and tryptamine derivatives in our work. Therefore, the observed potencies cannot be explained by the increase in the chain length of the radicals, since there were oscillations in the insecticidal action.…”
Section: Discussionmentioning
confidence: 46%